DEVELOPING COMPUTER ASSISTED LISTENING AND SPEAKING MATERIALS FOR ENGLISH FOR WAITER AND WAITRESS FOR FIRST SEMESTER STUDENTS OF FOOD AND BEVERAGE SERVICE DEPARTMENT IN MEDITERRANEAN BALI HOTEL SCHOOL - ., LUH GEDE MEITHA TRISNA UTAMI; ., PROF. DR. I NYM. ADI JAYA PUTRA, M.A.; ., DR. ASRIL MARDJOHAN, MA. (Jurnal Pendidikan Bahasa Inggris Indonesia, 2017)
Penelitian ini bertujuan untuk membuat materi Bahasa Inggris Listening dan Speaking berbasis computer untuk membantu siswa jurusan pramu saji semester pertama pada departemen Food and Beverage Service di Mediterranean Bali Hotel School. Berdasarkan data yang diperoleh di Mediterranean Bali Hotel School, proses belajar mengajar Listening dan Speaking belum dilengkapi dengan materi Bahasa Inggris yang Innovatif. Subjek dari penelitian ini adalah 20 siswa semester pertama dari kelas Food and Beverage Service A. Penelitian ini adalah penelitian Deskriptif Kualitatif. Penelitian ini mengdopsi model penelitian R&D oleh Dick and Carrey (1991) dengan tahap yang lebih disederhanakan dikarenakan waktu penelitian yang terbatas. Data penelitian ini dikumpulkan dengan lima jenis instrument yaitu: lembar observasi, kuisioner, pedoman wawancara, rubric dan catatan selama penelitian yang meliputi: analisis kebutuhan, penyusunan materi, dan evaluasi materi. Hasil dari penelitian ini adalah materi pembelajaran yang ditampilkan menggunakan media computer dalam bentuk Power Point.Kata Kunci : Pembelajaran Berbasis Komputer, Pengembangan Materi, Listening, Speaking This study aimed at developing Computer Assisted Listening and Speaking Materials for English for Waiter and Waitress for the first semester student of Food and Beverage Service Department of Mediterranean Bali Hotel School. Based on the data obtained in Mediterranean Bali Hotel School, it was found that the teaching and learning Listening and Speaking process were not supported by innovative English materials. The subjects of this study were 20 students of the first semester of Food and Beverage Service A. It was a descriptive qualitative study. The study adopted R&D model proposed by Dick and Carrey (1991) with a slightly shorten step in the implementation due to the limitation of time. The data were obtained by using five instruments: observation sheets, questionnaires, interview guidelines, rubrics and document researcher’s diary in the process of data collection, it included need analysis, material development and materials evaluation. The result of the materials was in form of a computerized learning media presented by Power Point.keyword : Computer Assisted Learning, Material Development, Listening, Speaking